Juridical Testimony Testimonium De Auditu And Unus Testis Nullus Testis In The Disclosure Of Criminal Offenses To Children - Ismawati Septiningsih; Itok Dwi Kurniawan; Muhammad Alif Daffa Putranto (Veteran Justice Journal, 2020)
This study aims to determine how the utilization of the Testimonium De Auditu testimony and the Unus Testis Nullus Testis can be legally justified in the disclosure of the crime of sexual abuse of children. This legal research method is normative or doctrinal legal research. The main data source is secondary data, which includes primary legal materials, secondary legal materials and tertiary legal materials. Data analysis uses data analysis techniques that are legal interpretations so that conclusions that are objective and systematic are obtained as answers to the problems studied. The results showed that the testimony of Testimonium De Auditu and unus testis nullus can be used to reveal criminal acts with additional evidence, in order to increase the judge's conviction to issue a decision.